Memristor based on molybdenum-doped vanadium dioxide phase change thin film material and preparation method thereof
By doping molybdenum into the VO2 film, MoxV1-xO2 phase change film material was prepared and the electrode structure was optimized, which solved the problems of VO2 stability and phase change temperature in low-power memristors, achieving higher stability and lower power consumption.
Patent Information
- Application Number
- CN202411751725.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-02
AI Technical Summary
The application of VO2 in memristors faces challenges such as poor stability and high phase transition temperature, especially in low-power devices.
MoxV1-xO2 phase change film material is prepared by doping molybdenum (Mo) into vanadium dioxide (VO2) film, and the stability of the memristor is improved by optimizing the electrode structure and size of the phase change switch.
Mo doping significantly reduces the phase transition temperature of VO2, improves its conductivity characteristics, making it more suitable for switching applications with low-power memristors, improves device stability and integration while reducing power consumption.
Smart Images

Figure CN119562756A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of phase change film and memristor preparation, specifically, using MoxV1-xO2 thin film material as the main functional layer of the memristor and optimizing the electrode structure and size of the phase change switch to improve the stability of the memristor. Background Art
[0002] Driven by the current development of informatization and intelligence, traditional storage technology is gradually approaching physical limits and cannot meet the demand for higher storage density and energy efficiency. As a new type of memory, memristor has become a research hotspot with its simple structure, low power consumption and integrated storage and computing advantages, providing important support for artificial intelligence hardware and neuromorphic computing. Memristor can achieve data storage by adjusting the resistance state and has synaptic-like characteristics.
[0003] VO2 is one of the ideal candidates for memristor materials due to its unique insulator-metal phase transition properties. VO2 undergoes a phase transition at a specific threshold voltage or temperature, resulting in a significant change in resistance, and has the potential to build a memristor. However, the practical application of VO2 faces challenges such as poor stability and high phase transition temperature, which is particularly evident in low-power devices. Therefore, doping technology has become an important means to improve the performance of VO2 in order to optimize its performance in memristors. Summary of the invention
[0004] The object of the present invention is to provide a memristor based on Mo-doped vanadium dioxide phase change thin film material to improve the stability of the switch and reduce power consumption.
[0005] The technical solution to achieve the first object of the present invention is: A method for preparing a Mo-doped vanadium dioxide phase change thin film material comprises the following specific steps: Step 1: Pretreatment of Si-based substrate materials, including cleaning and drying, using ethanol, acetone and ionized water for ultrasonic cleaning for 5 to 15 minutes, and finally drying with high-purity nitrogen; Step 2: Preparation for magnetron sputtering: Use metal V target and Mo target with a purity of 99.99%, install them on the DC sputtering target respectively, fix the Si-based substrate material on the sample tray, and evacuate the chamber of the high vacuum magnetron sputtering system, and use high-purity argon and oxygen as sputtering gases; wherein, the magnetron sputtering chamber is evacuated to ≤5×10-5 Pa, the volume percentage of high-purity argon is ≥99.999%, and the volume percentage of high-purity oxygen is ≤1%; Step 3: Magnetron sputtering MoxV1-xO2 thin film material: Step 3.1: Open the metal V target and Mo target baffles, introduce high-purity argon and oxygen; turn on the DC power supply, and pre-sputter for 1 to 5 minutes; Step 3.2: Use the co-sputtering deposition method to set the sputtering power of the V target and the Mo target; open the sample baffle for sputtering; after the sputtering is completed, close the sample baffle, the DC power supply and the target baffle to obtain an amorphous MoxV1-xO2 (0<x<1) phase change film; Step 4: Heat treatment of MoxV1-xO2 film: place the amorphous film in a tubular furnace for annealing; obtain the molybdenum-doped vanadium dioxide phase change thin film material MoxV1-xO2; its thickness is 90-180 nm; roughness is <5 nm; wherein the heat treatment is carried out in an atmosphere of high-purity argon gas throughout the process; the argon gas flow rate is 60-100 sccm, the temperature is 400-450 ℃, keep warm for 30-60 min, and cool to room temperature.
[0006] Before heat treatment, clean the pipeline to prevent sample oxidation; first evacuate the tube furnace, then replace it with a large amount of argon gas, and repeat 2 to 3 times; the heating rate of heat treatment is 5 to 10 ℃ / min, and the cooling process cools to room temperature with the furnace.
[0007] The technical solution for achieving the second object of the present invention is: A memristor based on molybdenum-doped vanadium dioxide phase change thin film material, the memristor comprises, from bottom to top, a Si substrate, a cross mark layer, a MoxV1-xO2 phase change thin film material layer and a top electrode layer; the preparation steps thereof include: Step 1: Pretreatment of Si-based substrate materials; Step 2: Prepare the mark layer: select a high-resistance single-crystal Si with a 90-300 nm thick SiO2 layer on the surface as the substrate, clean, blow dry, and spin-coat the substrate with photoresist, and then use electron beam lithography to pattern the cross mark layer on the substrate, then deposit 2-10 nm thick Cr and 40-100 nm thick Au by magnetron sputtering, and use acetone solution to remove the excess material to obtain the mark layer; Step 3: Prepare a MoxV1-xO2 thin film material layer: Spin-coat a photoresist on the mark layer, perform electron beam lithography to pattern the phase change material layer according to the cross mark alignment, deposit a 90-180 nm thick MoxV1-xO2 thin film material by magnetron sputtering, use an acetone solution to remove the excess material, obtain a MoxV1-xO2 thin film material layer, and perform heat treatment; Step 4: Prepare the top electrode layer: spin-coat photoresist on the MoxV1-xO2 thin film material layer, perform electron beam lithography to pattern the top electrode layer according to the cross mark alignment, deposit 2 to 10 nm thick Cr and 40 to 100 nm thick Au by magnetron sputtering, remove excess material with acetone solution to obtain the top electrode layer, and obtain the memristor based on the molybdenum-doped vanadium dioxide phase change thin film material.
[0008] In step 1, the pretreatment of the Si-based substrate material includes cleaning and drying; the cleaning process is to first ultrasonically clean the Si-based substrate material in an ethanol solution for 5 to 15 minutes, then ultrasonically clean it in an acetone solution for 5 to 15 minutes, and finally ultrasonically clean it with deionized water for 5 to 15 minutes, and after ultrasonic cleaning, use high-purity nitrogen to blow dry.
[0009] In step 3, the heat treatment of the MoxV1-xO2 phase change thin film material layer is carried out in an atmosphere of high-purity argon gas with an argon gas flow rate of 80 to 100 sccm, at 400 to 450 °C for 30 to 60 min, at a heating rate of 5 to 10 °C / min, and finally cooled to room temperature with the furnace.
[0010] The Mo-doped VO2 phase-change thin film memristor is characterized in that the overall structural size of the device is ≤5×10 μm; and the channel width between the top electrodes is 0.6-2.0 μm.
[0011] The present invention can significantly reduce the phase change temperature of VO2 and improve its conductivity characteristics through Mo doping, making it more suitable for switching applications of low-power memristors. Mo doping not only improves the phase change controllability and stability of VO2 thin films, but also effectively reduces the working power consumption of the device.
[0012] Compared with the prior art, the present invention has the following beneficial effects: The memristor of the present invention is based on MoxV1-xO2 phase change thin film material as the main switch function layer, and has a lower phase change temperature and a wider thermal hysteresis range; the present invention adopts a top electrode structure, which is more concise and easy to integrate; by reducing the electrode channel width and device size, the heating efficiency is further improved, thereby reducing power consumption. The present invention can improve the stability and integration of the memristor, reduce power consumption, and provide an innovative idea for the development of a new high-speed memristor array. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 A curve diagram showing the relationship between resistance and temperature of the MoxV1-xO2 phase change thin film material and the VO2 phase change thin film material of the present invention; Figure 2 This is a schematic diagram of the structure of a memristor based on MoxV1-xO2 phase change thin film material of the present invention; Figure 3 It is a schematic flow chart of a method for preparing a memristor based on MoxV1-xO2 phase change thin film material according to the present invention; Figure 4 This is a test diagram of the room temperature threshold switching characteristics of the memristor based on the MoxV1-xO2 phase change thin film material of the present invention. DETAILED DESCRIPTION
[0014] In the following description, specific details such as specific system structures, technologies, etc. are provided for illustration rather than limitation, so as to provide a thorough understanding of the embodiments of the present invention. However, it should be clear to those skilled in the art that the present invention may be implemented in other embodiments without these specific details. In other cases, detailed descriptions of well-known structures, materials, and methods are omitted to prevent unnecessary details from hindering the description of the present invention.
[0015] In order to illustrate the technical solution of the present invention, a specific embodiment is provided below for illustration. Example
[0016] A method for preparing a Mo-doped vanadium dioxide phase-change thin film material.
[0017] Preparation process of Mo-doped VO2 phase change thin film material: On a Si substrate, a 99.99% pure metal V target and a Mo target are co-sputtered to deposit an amorphous MoxV1-xO2 thin film. The total thickness of the thin film material is 90 to 180 nm.
[0018] The Mo-doped vanadium dioxide phase change thin film material of this embodiment is prepared by magnetron sputtering, and the specific preparation method includes the following steps: (1) Pretreatment of Si-based substrate materials: The Si-based substrate materials were first ultrasonically cleaned in an ethanol solution for 15 minutes, then ultrasonically cleaned in an acetone solution for 15 minutes, and finally ultrasonically cleaned in deionized water for 10 minutes. After ultrasonic cleaning, they were blown dry with high-purity nitrogen gas; (2) Preparation for magnetron sputtering: The V target and the Mo target were respectively mounted on the DC sputtering target, the Si-based substrate was fixed on the sample tray, and the chamber of the high vacuum magnetron sputtering system was evacuated to 5×10-5 Pa. The volume ratio of argon and oxygen in the sputtering atmosphere was 100:1, the argon flow rate was 100 sccm, and the oxygen flow rate was 1 sccm. During the sputtering process, the vacuum degree of the magnetron sputtering chamber was 0.6 Pa. (3) Magnetron sputtering of MoxV1-xO2 phase change thin film material: Open the V target and Mo target baffles, turn on the DC power supply, set the sputtering power to 60 W and 1 W respectively, pre-sputter for 3 min, and formally sputter for 20 min to obtain an amorphous Mo0.014V0.986O2 phase change film with a thickness of 100 nm. After sputtering, close the sample baffle, DC power supply and target baffle; (4) Heat treatment of Mo0.014V0.986O2 phase change film: The obtained amorphous film was placed in a tube furnace and annealed at 450 °C for 60 min with an argon flow rate of 80 sccm and a heating rate of 10 °C / min, and then naturally cooled to room temperature.
[0019] Comparative Example 1 A high-quality vanadium dioxide film is prepared as follows: (1) Pretreatment of Si-based substrate material: the cleaning steps are the same as those in Example 1; (2) Preparation for magnetron sputtering: A metal V target with a purity of 99.99% was used and installed on a DC sputtering target. The Si-based substrate material was fixed on a sample tray. The vacuum degree of the sputtering chamber was 5×10-5 Pa. The volume ratio of argon and oxygen in the sputtering atmosphere was 100:1. The argon flow rate was 100 sccm, and the oxygen flow rate was 1 sccm. During the sputtering process, the vacuum degree of the magnetron sputtering chamber was 0.6 Pa. (3) Magnetron sputtering of VO2 phase change thin film material: Open the V target baffle, set the DC power supply sputtering power to 60 W, pre-sputter for 3 min, and formal sputter for 20 min to obtain an amorphous VO2 phase change film with a thickness of 100 nm; (4) Heat treatment of VO2 phase change film: The obtained amorphous film was placed in a tube furnace, annealed at 450 °C for 60 min, with an argon flow rate of 80 sccm and a heating rate of 10 °C / min, and then cooled to room temperature.
[0020] Related performance tests The resistance-temperature relationship of the MoxV1-xO2 phase change thin film material prepared in Example 1 and the VO2 phase change thin film material prepared in Comparative Example 1 was tested. The results are as follows: Figure 1 As shown in the figure, the heating rate during the test is 5 ℃ / min. The test shows that the phase transition temperature of VO2 phase change thin film material is 69.7 ℃, while the phase transition temperature of MoxV1-xO2 phase change thin film material is 49 ℃. Example
[0021] A memristor based on Mo-doped vanadium dioxide phase change thin film material, such as Figure 2 As shown, from bottom to top, it includes: a Si substrate, a Mark layer, a MoxV1-xO2 phase change thin film material layer and a top electrode layer.
[0022] The memristor based on Mo-doped vanadium dioxide phase change thin film material of this embodiment is prepared as follows Figure 3 As shown, the specific preparation method comprises the following steps: (a) Pretreatment of Si-based substrate material: the same as in Example 1; (b) Preparation of mark layer: A high-resistance single-crystal Si with a 300 nm thick SiO2 layer on the surface was selected as the substrate. After the substrate was cleaned, dried, and spin-coated with photoresist, a cross-marked mark layer was patterned by electron beam lithography. Then, 10 nm thick Cr and 40 nm thick Au were deposited by magnetron sputtering. The excess material was removed by soaking and cleaning with an acetone solution to obtain a mark layer. (c) preparing a MoxV1-xO2 phase change thin film material layer: spin coating a photoresist on the mark layer, performing electron beam lithography to pattern the phase change material layer according to the cross mark alignment, depositing a 100 nm thick Mo0.014V0.986O2 thin film material by magnetron sputtering according to the preparation method in Example 1, and removing excess material by soaking in an acetone solution to obtain a phase change material layer; and then performing a heat treatment on the layer; (d) Preparation of top electrode layer: Spin-coating photoresist on the Mo0.014V0.986O2 phase change thin film material layer, performing electron beam lithography to pattern the top electrode layer according to the cross mark alignment, depositing 10 nm thick Cr and 40 nm thick Au by magnetron sputtering, and removing excess material by soaking in acetone solution to obtain the top electrode layer, and the channel width between the electrodes is 1.5 μm; Figure 4 The test results of threshold switching characteristics of the memristor based on Mo0.014V0.986O2 phase change thin film material at room temperature are demonstrated.
[0023] The embodiments described above are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the embodiments described above, those skilled in the art should understand that the technical solutions described in the embodiments described above can still be modified, or some of the technical features can be replaced by equivalents. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention, and should all be included in the protection scope of the present invention.
Claims
1. A method for preparing a molybdenum-doped vanadium dioxide phase change thin film material, characterized in that: The method comprises the following specific steps: Step 1: Pretreatment of Si-based substrate materials, including cleaning and drying, using ethanol, acetone and ionized water for ultrasonic cleaning for 5 to 15 minutes, and finally drying with high-purity nitrogen; Step 2: Preparation for magnetron sputtering: Use metal V target and Mo target with a purity of 99.99%, install them on the DC sputtering target respectively, fix the Si-based substrate material on the sample tray, and evacuate the chamber of the high vacuum magnetron sputtering system, and use high-purity argon and oxygen as sputtering gases; wherein, the magnetron sputtering chamber is evacuated to ≤5×10-5 Pa, the volume percentage of high-purity argon is ≥99.999%, and the volume percentage of high-purity oxygen is ≤1%; Step 3: Magnetron sputtering MoxV1-xO2 thin film material: Step 3.1: Open the metal V target and Mo target baffles, introduce high-purity argon and oxygen; turn on the DC power supply, and pre-sputter for 1 to 5 minutes; Step 3.2: Use the co-sputtering deposition method to set the sputtering power of the V target and the Mo target; open the sample baffle for sputtering; after the sputtering is completed, close the sample baffle, the DC power supply and the target baffle to obtain an amorphous MoxV1-xO2 phase change film, wherein 0<x<1; Step 4: Heat treatment of MoxV1-xO2 film: place the amorphous film in a tubular furnace for annealing; obtain the molybdenum-doped vanadium dioxide phase change thin film material MoxV1-xO2; its thickness is 90-180 nm; roughness is <5 nm; wherein the heat treatment is carried out in an atmosphere of high-purity argon gas throughout the process; the argon gas flow rate is 60-100 sccm, the temperature is 400-450 ℃, keep warm for 30-60 min, and cool to room temperature.
2. The preparation method according to claim 1, characterized in that: In the heat treatment described in step 4, the pipeline is cleaned before the heat treatment to prevent the sample from being oxidized; the tube furnace is first evacuated, and then replaced with a large amount of argon gas, and repeated 2 to 3 times; the heating rate of the heat treatment is 5 to 10 °C / min, and the cooling process is cooled to room temperature with the furnace.
3. A memristor based on molybdenum-doped vanadium dioxide phase change thin film material, characterized in that: The memristor comprises, from bottom to top, a Si substrate, a cross mark layer, a MoxV1-xO2 phase change thin film material layer and a top electrode layer; and its preparation steps include: Step 1: Pretreatment of Si-based substrate materials; Step 2: Prepare the mark layer: select a high-resistance single-crystal Si with a 90-300 nm thick SiO2 layer on the surface as the substrate, clean, blow dry, and spin-coat the substrate with photoresist, and then use electron beam lithography to pattern the cross mark layer on the substrate, then deposit 2-10 nm thick Cr and 40-100 nm thick Au by magnetron sputtering, and use acetone solution to remove the excess material to obtain the mark layer; Step 3: Prepare a MoxV1-xO2 thin film material layer: Spin-coat a photoresist on the mark layer, perform electron beam lithography to pattern the phase change material layer according to the cross mark alignment, deposit a 90-180 nm thick MoxV1-xO2 thin film material by magnetron sputtering, use an acetone solution to remove the excess material, obtain a MoxV1-xO2 thin film material layer, and perform heat treatment; Step 4: Prepare the top electrode layer: spin-coat photoresist on the MoxV1-xO2 thin film material layer, perform electron beam lithography to pattern the top electrode layer according to the cross mark alignment, deposit 2 to 10 nm thick Cr and 40 to 100 nm thick Au by magnetron sputtering, remove excess material with acetone solution to obtain the top electrode layer, and obtain the memristor based on the molybdenum-doped vanadium dioxide phase change thin film material.
4. The memristor according to claim 3, characterized in that: The overall structural size of the memristor is ≤5×10 μm; the channel width between the top electrodes is 0.6-2 μm.
Citation Information
Patent Citations
Low-temperature high-resistance temperature coefficient non-heat stagnation thin-film material and preparation method thereof
CN103540903A
Method for preparing titanium-doped vanadium oxide film with no phase transformation and high resistance temperature coefficient
CN104178738A
Method for reducing phase change temperature of vanadium dioxide film
CN104445990A
Preparation method of tungsten-doped vanadium dioxide film with adjustable phase change temperature
CN112921291A
Amorphous molybdenum-doped tungsten oxide electrochromic material and preparation method thereof
CN116445872A
Cited By
Neuromorphic memristor doped with vanadium oxide and manufacturing method and application of neuromorphic memristor
CN120187278A